Brain activity changes associated with treadmill training after stroke. - Enzinger, C; Dawes, H; Johansen-Berg, H; Wade, D; Bogdanovic, M; Collett, J; Guy, C; Kischka, U; Ropele, S; Fazekas, F; Matthews, P (2009)
BACKGROUND AND PURPOSE: The mechanisms underlying motor recovery after stroke are not fully understood. Several studies used functional MRI longitudinally to relate brain activity changes with performance gains of the upper limb after therapy, but research into training-induced recovery of lower limb function has been relatively neglected thus far. METHODS: We investigated functional reorganization after 4 weeks of treadmill training with partial body weight support in 18 chronic patients (mean age, 59.9+/-13.5 years) with mild to moderate paresis (Motricity Index affected leg: 77.7+/-10.5; range, 9 to 99) and gait impairment (Functional Ambulation Category: 4.4+/-0.6; range, 3 to 5) due to a single subcortical ischemic stroke using repeated 3.0-T functional MRI and an ankle-dorsiflexion paradigm. RESULTS: Walking endurance improved after training (2-minute timed walking distance: 121.5+/-39.0 versus pre: 105.1+/-38.1 m; P=0.0001). For active movement of the paretic foot versus rest, greater walking endurance correlated with increased brain activity in the bilateral primary sensorimotor cortices, the cingulate motor areas, and the caudate nuclei bilaterally and in the thalamus of the affected hemisphere. CONCLUSIONS: Despite the strong subcortical contributions to gait control, rehabilitation-associated walking improvements are associated with cortical activation changes. This is similar to findings in upper limb rehabilitation with some differences in the involved cortical areas. We observed bihemispheric activation increases with greater recovery both in cortical and subcortical regions with movement of the paretic foot. However, although the dorsal premotor cortex appears to play an important role in recovery of hand movements, evidence for the involvement of this region in lower extremity recovery was not found.